Bible, interpretation, and context: reading meaning from an African perspective - Okorie, Ferdinand (Lexington Books/Fortress Academic, 2023)
Cover -- Contents -- Acknowledgments -- ‌‌Introduction -- Exploring the Prospect of Biblical Hermeneutics -- Catholic Interpretation of Scripture -- Where Shall Wisdom Be Found? (Job 28:12) -- Paul and Early Christianity in Teaching and Ministry -- Context and Biblical Hermeneutics -- African Feminist Approaches to the Bible -- God, Women, and Point of View in the Abraham and Jacob Narratives -- Reading Pentateuchal Ancestral Narratives in the Context of Community Identity in Africa‌‌‌ -- Hearing and Reading the "Rebuilding" Voice of the Prophet Haggai (1:1 - 11) in the Context of African Christianity -- Tobit's Almsgiving as a Model of Missionary Availability -- Earth, Cosmology, and Context in the Book of Revelation -- ‌‌Conclusion -- James Chukwuma Okoye, CSSp, Selected Bibliography -- Index -- About the Editors and Contributors.